PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRESTASI KERJA KARYAWAN PADA PT. PERTAMINA (PERSERO) MEDAN - Indra, Aulia (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2018)
Occupational Health and Safety (K3) is a system of programs designed for both workers and employers in an effort to prevent the occurrence of occupational accidents and diseases caused by working relations in the work environment by identifying the things that potentially cause workplace accidents and anticipatory action in the event of such a thing. The resulting impact of this workplace accidents can be bad, such as the loss of lives, disability, damage to production, which is ultimately detrimental to all parties. In Indonesia, every company has to follow the program of the Occupational Health and Safety (K3), but can be seen in workplace accidents are still common. The purpose of this research was to determine the effect of occupational safety and health (K3) on employee performance in PT. Pertamina (Persero) Medan. Digunakana research method is simple linear regression. The estimation deskriptif showed that is company an very important for health and safety (K3) on employee company and the health and safety (K3) positif and significant effect on employee performance in PT. Pertamina (Persero) Medan.